Penggunaan Mobile Base Station South Galaxy G1 untuk Pengukuran Batas Bidang Tanah di Kawasan Padat Bangunan - Wirapradeksa, Hanggas; Nugroho, Tanjung; Suhattanto, Muhammad Arif (Tunas Agraria, 2019)
Abstract: GNSS CORS as one of land and area measuring instrument has the weakness of limited range of base station and can only be used in open area. Nowadays, this weakness can be overcome by mobile base station technology. One GNSS tool that uses mobile base station technology is Galaxy G1, South type. Another advantage is that, it can capture the Beidou satellite signal so that the satellite configuration becomes better. Thus, the researcher conducted a study with the aims (1) to know the difference between accuracy of measurement MBS South Galaxy G1 with and without Beidou satellites; (2) to test the accuracy of the results of measurements using Mobile Base Station South Galaxy G1 type towards the results of measurements with Electronic Total Station (ETS) in the densely building area. This research used a comparison experimental research method with a quantitative approach. The results of the analysis show that (1) the coordinates of the observation with Beidou have an average horizontal accuracy of 0.025 m, while the results of the calculation of coordinates without Beidou have an average horizontal accuracy of 0.421 m. (2) The difference between the MBS South Galaxy G1 coordinate value and the terrestrial coordinate value is 0.132 m on average. The results of the t-test with a significance level of 5% found that the MBS South Galaxy G1 coordinate value has a significant difference to the terrestrial coordinate value. Keywords: mbs, south galaxy g1 Intisari: CORS sebagai salah satu alat ukur bidang tanah mempunyai kelemahan terbatasnya jangkauan base station dan hanya dapat digunakan di daerah terbuka. Kelemahan tersebut kini dapat diatasi dengan adanya teknologi MBS. Salah satu alat GNSS yang menggunakan teknologi MBS adalah South tipe Galaxy G1. Kelebihan lain adalah dapat menangkap sinyal satelit Beidou sehingga konstalasi satelitnya lebih baik. Berdasarkan hal tersebut peneliti ini bertujuan (1) mengetahui perbedaan ketelitian hasil pengukuran MBS South Galaxy G1 dengan dan tanpa satelit Beidou; (2) menguji ketelitian hasil pengukuran menggunakan MBS South Tipe Galaxy G1 terhadap hasil pengukuran dengan Electronik Total Station (ETS) pada kawasan padat bangunan. Metode yang digunakan adalah metode penelitian eksperimen perbandingan dengan pendekatan kuantitatif. Hasil analisis diketahui (1) Koordinat pengamatan dengan Beidou memiliki ketelitian horisontal rata-rata sebesar 0.025 m, sedangkan hasil perhitungan koordinat tanpa Beidou memiliki ketelitian horisontal rata-rata sebesar 0.421 m. (2) Perbedaan nilai koordinat MBS South Galaxy G1 terhadap nilai koordinat terestris rata-rata sebesar 0.132 m. Hasil uji t dengan taraf signifikansi 5% diperoleh bahwa nilai koordinat MBS South Galaxy G1 memiliki perbedaan yang signifikan terhadap nilai koordinat terestris. Kata Kunci: mbs, south galaxy g1.